Intergovernmental transfers to the Brazilian unified health system and party alignment - Veronica Ines Fernandez Orellano; Taís Cardoso Tellini (EconomiA, 2023)
Purpose: This study investigates the impact of political alignment on intergovernmental transfers to the Brazilian unified health system (SUS). The authors analyzed both automatic transfers based on pre-established rules and discretionary transfers, using two criteria of political alignment between mayors and the central government. Design/methodology/approach: For the empirical analysis the authors used regression-discontinuity design (RDD) and the outcomes of close elections between 2001 and 2017. Findings: The results indicate positive and statistically significant effects of party alignment on the two transfer categories, especially discretionary transfers, but also on transfers based on pre-established rules. The effect of direct party alignment, when mayors and the president are from the same party, is greater than that resulting from coalitions established in municipal and federal elections. Research limitations/implications The positive effect of party alignment was found both in discretionary transfers (those that do not have previously established rules) and some non-discretionary transfers (although they have previously defined regulations). A part of these regulations depends on production capacity and on taking part in programs promoted by the central government, which may produce entropy in the financing system, and a margin to benefit political allies. In the case of the SUS system, it is possible that this entropy is greater in the basic health care category than in the moderate and high complexity one, allowing a higher margin for discretion in transfers allocated to the former. Stricter rules associated to basic health care transfers would be desirable. Practical implications In Brazil, stricter rules and monitoring associated to basic healthcare intergovernmental transfers would be desirable. Social implications The results may inspire some improvement in the mechanisms that govern the distribution of resources to basic healthcare in Brazil, improving social welfare by improving social justice in the distribution of resources to basic healthcare. Originality/value: The authors does not know any other study about the impact of party alignment on the distribution of intergovernmental transfers to the Brazilian unified health system.
Keywords: H77; I18; 330; Intergovernmental transfers; Health care; SUS; Political alignment